Synergy of Forecast and Remote Sensing Data supporting an Arctic Research Cruise in the Beaufort Sea - Lehner, Susanne; Ressel, Rudolf; Pleskachevsky, Andrey; Gemmrich, Johannes (2016)
The field campaign of the “Sea State and Boundary Layer Physics on the Emerging Arctic” program, conducted aboard R/V Sikuliaq in October 2015 in the Beaufort Sea, aimed at understanding the role of surface waves and winds during the fall ice advance. During this period the ice edge advances on average about 20km/day, which is similar to the spatial coverage of high-resolution space-borne SAR modes (e.g. TerraSAR-X, Radarsat 2). Deciding on locations for various in-situ observations at the ice edge, within a 1-3 day window was based on a large suite of SAR and visible remote sensing products as well as atmospheric, wave and ice model forecast contracted from highly detailed purpose-run forecast to predictions taken from freely available sources. Based on the wide variety of available Arctic remote sensing and model forecast products, one of the main challenges is to select and condense the information that can be transferred to the ship, given a limited bandwidth for regular data transfer. During this cruise, a stratified approach was tested where the shore team collected a large set of products, many in different resolutions, from which the ship team prioritized their data access on a daily Basis.